Hurricane Katrina rescue - Messner, Kate; McMorris, Kelley (New York : Scholastic Inc., 2018)
When the mysterious first aid kit takes golden retriever Ranger to New Orleans shortly before Hurricane Katrina hits, he finds himself helping Clare Porter and her grandmother, who are waiting for Clare's father at their home in the Lower Ninth Ward--and when the levees break and Clare is separated from Nana, Ranger must somehow get her to the relative safety of the Superdome, and reunite her with her family.
Includes bibliographical references.
4.4
3-6
560L
Keywords: Hurricane Katrina, 2005 -- Fiction; Golden retriever -- Fiction; Dogs -- Fiction; Family life -- Louisiana -- New Orleans -- Fiction; New Orleans (La.) -- Fiction; Action and adventure fiction; Time-travel fiction